POSSIBILITIES OF ELECTRONIC CONFERENCE CREATION BY PLATFORM OPEN CONFERENCE SYSTEMS: VIEW OF LIBRARIAN - Pominova, Olga V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The report describes the possibilities of open access electronic conferences on the basis of the platform Open Conference Systems (OCS) in higher educational institutions. There is presents the role of university libraries in these processes. Considered gradual creation of websites of Dnipropetrovsk National University of Railway Transport named after Academician V. Lazaryan (DNURT) scientific conferences. Notes advantages of using OCS.